2015
DOI: 10.1111/tbed.12374
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Genome Analysis of a Lineage III Peste Des Petits Ruminants Virus in Kenya in 2011

Abstract: In May 2011 in Turkana County, north-western Kenya, tissue samples were collected from goats suspected of having died of peste des petits ruminant (PPR) disease, an acute viral disease of small ruminants. The samples were processed and tested by reverse transcriptase PCR for the presence of PPR viral RNA. The positive samples were sequenced and identified as belonging to peste des petits ruminants virus (PPRV) lineage III. Full-genome analysis of one of the positive samples revealed that the virus causing dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Many of the characteristics previously identified in other PPRV proteins were seen in Benin/10/2011 and Benin/B1/1969 (Dundon et al., ,b, , ). These include the nuclear export signal (4‐LLKSLALF‐11) and nuclear localization signal (70‐TGVMISML‐77) motifs involved in the transport of the N protein to the nucleus of the host cell, putative N protein phosphorylation sites, a tyrosine residue at position 110 of the V protein, known to be involved in specific binding of the signal transducer and activator of transcription I (STAT1) in MV and canine distemper virus (CDV), and the F protein cleavage site (GRRTRR) and potential glycosylation sites (NLS 25–27, NIT 57–59 and NCT 63–65).…”
Section: Resultsmentioning
confidence: 79%
“…Many of the characteristics previously identified in other PPRV proteins were seen in Benin/10/2011 and Benin/B1/1969 (Dundon et al., ,b, , ). These include the nuclear export signal (4‐LLKSLALF‐11) and nuclear localization signal (70‐TGVMISML‐77) motifs involved in the transport of the N protein to the nucleus of the host cell, putative N protein phosphorylation sites, a tyrosine residue at position 110 of the V protein, known to be involved in specific binding of the signal transducer and activator of transcription I (STAT1) in MV and canine distemper virus (CDV), and the F protein cleavage site (GRRTRR) and potential glycosylation sites (NLS 25–27, NIT 57–59 and NCT 63–65).…”
Section: Resultsmentioning
confidence: 79%
“…The initial introduction of PPR into Kenya's Turkana region in 2006 was confirmed and reported to the OIE in 2007 (OIE WAHIS). There is no molecular epidemiological investigation reported in the literature that allows one to conclusively determine the lineage of the virus of this initial introduction in 2006, although in 2012 a study reported that viruses circulating in Uganda, Tanzania and Kenya were all of the same origin and were Lineage III (Dundon et al., ). This 2006/2007 event occurred simultaneously with multiple social and political events that resulted in the movement of people into Northwest Kenya, leading to an increased demand for food and thus the movement of livestock (UNHCR Kenya Global Report, ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, a study by Dundon et al. () sampled goats from Turkana County (the origin of the PPRV outbreak) in Kenya. These samples were sequenced and shown to belong to lineage III.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary PPRV H and F cDNAs were amplified from viral RNA. PPRV containing supernatants from cultures of PPRV isolates Senegal 1969 [26] (lineage I), Benin 2010 [27] (lineage II), Kenya 2011 [28] (lineage III) and Ethiopia 2010 (lineage IV, Joint FAO/IAEA PPRV Bank, Seibersdorf, Austria) were mixed with RLT lysis buffer (QIAgen) and RNA prepared as per manufacturer’s instructions using a QIAamp Viral RNA Mini kit (QIAgen). This RNA was then used to prepare first strand cDNA (Transcriptor First Strand cDNA Synthesis Kit, Roche) and used as a template in PCR reactions using Q5 high fidelity DNA polymerase (see Supplementary Methods for details of primers).…”
Section: Methodsmentioning
confidence: 99%